Inclusive Economic Development Through Unemployment Analysis of Educated Young People Between Islands in Indonesia - Hidayah; Nazer, Muhammad; Maryati, Sri (Economic Education Analysis Journal, 2024)
This research aims to analyze the risk of individuals between islands in Indonesia becoming unemployed among educated young people. This is researched because not always those who have higher education and are young will get a job. Apart from that, Indonesia, which consists of many islands, has differences in unemployment among educated youth. This research is quantitative in nature using micro data from the August 2021 National Labor Force Survey (Sakernas) with the workforce population in Indonesia aged 15-24 years and a sample of 79.362 technical data analysis using Logistic Regression.The results of the research show that all regional classification variables, position in the household, gender, marital status, training, work experience, education major, disability and education provider have a significant effect on unemployment among educated youth in Indonesia. The results of research on unemployment among educated young people between islands in Indonesia experience variations. With the differences in unemployment outcomes for educated youth between islands in Indonesia, it is necessary to equalize economic development between islands in Indonesia, so as to create equal prosperity in Indonesia and create inclusive economic development in Indonesia.